2015
DOI: 10.1177/0143034315574153
|View full text |Cite
|
Sign up to set email alerts
|

Treatment acceptability of interventions published in six school psychology journals

Abstract: Treatment acceptability (TA) is critical when selecting and implementing an intervention, as TA is associated with treatment outcomes. The significance of TA is reflected in school psychology models for services that state that school psychologists should address TA during development, implementation, and evaluation of interventions. However, the understanding of TA as it pertains to issues relevant to school psychologists is limited by the lack of analyses of the reporting of TA in intervention research. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
3
16
0
1
Order By: Relevance
“…Assessing for acceptability is one method to determine if a socially important outcome was achieved (Kazdin, ). To better understand if interventions are meeting this indicator, acceptability should be measured in the intervention literature, though past reviews suggest it is infrequently reported (e.g., Villarreal, Ponce, & Gutierrez, ). This issue may be because a standardized approach to the assessment and reporting of acceptability continues to be absent from many applied research journal guidelines (Callahan et al, ; Roach, Wixson, Talapatra, & LaSalle, ) despite recommendations to include acceptability in professional practice and research.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing for acceptability is one method to determine if a socially important outcome was achieved (Kazdin, ). To better understand if interventions are meeting this indicator, acceptability should be measured in the intervention literature, though past reviews suggest it is infrequently reported (e.g., Villarreal, Ponce, & Gutierrez, ). This issue may be because a standardized approach to the assessment and reporting of acceptability continues to be absent from many applied research journal guidelines (Callahan et al, ; Roach, Wixson, Talapatra, & LaSalle, ) despite recommendations to include acceptability in professional practice and research.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of children in the current study reported a similar experience of generally feeling better and more relaxed after doing the TRIPLE R program. Positive affect towards an intervention program is a strong indicator of program acceptability (Villarreal et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential value of acceptability data and more specifically, qualitative acceptability data, there is a paucity of such research (Villarreal et al 2015). Acceptability data has been positively associated with efficacy data in intervention research (Eckert and Hintze 2000).…”
Section: Program Evaluation and Acceptabilitymentioning
confidence: 99%
See 2 more Smart Citations